Exploring the Effect of Product Quality, Service Quality, and Social Media Advertisement on Customer Loyalty in Choosing Alligator Roastery - Denzel Linardo (MultiTech Publisher, 2020)
This study investigates the interplay of product quality, service quality, and social media advertising within the context of Alligator Roastery, aiming to discern their collective impact on customer loyalty. Employing a comprehensive research approach, including surveys, interviews, and data analysis, the findings indicate a significant positive association between product quality and customer loyalty, alongside the pivotal role of attentive service quality. Moreover, effective social media advertising emerges as a potent tool for attracting and retaining customers, underscoring the interconnectedness of these factors in shaping customer loyalty, thereby providing valuable insights for Alligator Roastery and similar businesses in enhancing their competitive positioning and fostering lasting customer relationships